2022
DOI: 10.3390/bios12100834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Chest-Worn Accelerometer and Gyroscope Performance for Heart Rate and Respiratory Rate Monitoring

Abstract: The demand for wearable devices to simultaneously monitor heart rate (HR) and respiratory rate (RR) values has grown due to the incidence increase in cardiovascular and respiratory diseases. The use of inertial measurement unit (IMU) sensors, embedding both accelerometers and gyroscopes, may ensure a non-intrusive and low-cost monitoring. While both accelerometers and gyroscopes have been assessed independently for both HR and RR monitoring, there lacks a comprehensive comparison between them when used simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…Additionally, further efforts will be devoted to investigating the effect of respiration in HRV analysis. As it has already been demonstrated that a single IMU sensor on the chest is able to capture the respiratory rate [ 21 ], in the future we will investigate how the contextual assessment of this vital parameter can help to provide a more accurate assessment of HRV indexes (especially in the frequency domain), which has only been partially demonstrated with studies on a limited number of subjects during ECG monitoring [ 60 , 61 ]. Lastly, the study was conducted only under resting conditions, so motion artifacts that could adversely affect the results were inherently eliminated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, further efforts will be devoted to investigating the effect of respiration in HRV analysis. As it has already been demonstrated that a single IMU sensor on the chest is able to capture the respiratory rate [ 21 ], in the future we will investigate how the contextual assessment of this vital parameter can help to provide a more accurate assessment of HRV indexes (especially in the frequency domain), which has only been partially demonstrated with studies on a limited number of subjects during ECG monitoring [ 60 , 61 ]. Lastly, the study was conducted only under resting conditions, so motion artifacts that could adversely affect the results were inherently eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…A single IMU (Xsens DOT by Xsens, The Netherlands) was attached with a hypoallergenic medical-grade double-sided tape at the xiphoid process level. Among the numerous body landmarks used to collect cardiac-related acceleration signals, we used the xiphoid because of good inter-subject reliability and easy identification of the body [ 21 , 22 ]. The selected IMU sensor has different features that make it ideal in this scenario.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such devices are typically inexpensive, unobtrusive, resistant to electromagnetic and acoustic interferences, safe and viable for prolonged use, since they commonly have an extremely low power consumption [23]. Actually, SCG and GCG techniques are rapidly spreading in medical scenarios as alternatives to ECG for monitoring the pre-and post-procedural conditions of patients [25], allowing to estimate hemodynamic parameters that can be hardly recovered using other sensing techniques [26], [27]. Several other applications, including posture analysis and context retrieval, have been also designed using chest-worn inertial sensors [28].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them used a hydraulic sensor system filled with water [17], load cells [18], piezoelectric load [19], pressure sensors installed under the mattress [20,21] and others. With the development of highly sensitive accelerometers based on micro-electromechanical systems (MEMS), their application in various measurement fields is growing rapidly [22][23][24][25]. Unfortunately, using accelerometers to measure BCG signals remains an understudied area of metrology [13,26,27].…”
Section: Introductionmentioning
confidence: 99%